EVALUASI PENERAPAN WITHHOLDING TAX SYSTEM TERHADAP PAJAK PENGHASILAN PASAL 21 PADA PEGAWAI TETAP PT TASPEN (PERSERO) KANTOR CABANG MANADO - Puapadang, Yohana Regin Seyni; Elim, Inggriani; Pangerapan, Sonny (Universitas Sam Ratulangi, 2021)
Taxes are one of the largest sources of revenue in the APBN, so it has a very important role in financing the country. Withholding Tax System is a tax collection system which authorizes of third parties to determine the amount of tax payable by the taxpayer and is responsible for depositing and reporting the tax payable. Income Tax Article 21 is one of tax type that uses the Withholding Tax System. This research was conducted on permanent employees of PT Taspen (Persero) Branch Office Manado. The purpose of this research is to evaluating how the application of Withholding Tax System to Income Tax Article 21 on permanent employees of PT Taspen (Persero) Branch Office Manado is in accordance with Laws Number 36 of 2008 Article 17a, PMK Number 242/PMK.03/2014, and DJP PER-16/PJ/2016 Article 24. The results of this research that has been conducted on permanent employees of PT Taspen (Persero) Branch Office Manado obtained show that the application of the Withholding Tax System in terms of calculation, deduction, deposit and reporting of Income Tax Article 21 on permanent employees of PT Taspen (Persero) Branch Office Manado is in accordance with the current taxation laws.